REPOSISI DAN REAKTUALISASI PENDIDIKAN MADRASAH DALAM MEMPERKUAT EKSISTENSI PENDIDIKAN DI ERA 4.0 - Widyasari, Rully Rina; Mukhibat, Mukhibat (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2020)
Abstract: This article examines the repositioning and reactualization of madrassas in strengthening the existence of Islamic education in the 4.0 era. This means repositioning the madrasa by making changes and managing it as it is towards more professional management. So it is expected to be able to answer the challenges of the existence of Islamic education in the 4.0 era. Entering the revolutionary era 4.0 with its disruptive innovation, the implementation of Islamic education is free to choose to stay in the old system or try to open up in this era of disruption. The research method in this article is qualitative library research. Therefore, to maintain the existence of Islamic education and to place madrasa with its reactualization, by borrowing the term Rhenald Kasali, there are three steps that must be taken by Islamic education in the 4.0 era, namely disruptive mindset, self-driving, and reshape or create. Artikel ini mengkaji tentang reposisi dan reaktualisasi madrasah dalam memperkuat eksistensi pendidikan Islam di era 4.0. Artinya memposisikan kembali madrasah dengan melakukan perubahan dan pengelolaan yang apa adanya menuju kepengelolaan yang lebih professional. Sehingga diharapkan mampu menjawab tantangan eksistensi pendidikan Islam di era 4.0. Memasuki era revolusi 4.0 dengan disruptive innovation-nya penyelenggaraan pendidikan Islam bebas memilih untuk tetap pada sistem lama atau mencoba membuka diri di era disrupsi ini. Metode penelitian dalam artikel ini adalah kualitatif library research. Oleh sebab itu untuk menjaga eksistensi pendidikan Islam dan menempatkan madrasah dengan reaktualisasinya maka dengan meminjam istilah Rhenald Kasali, ada tiga langkah yang harus dilakukan oleh pendidikan Islam di era 4.0 yaitu disruptive mindset, self-driving, dan reshape or create.